2019
DOI: 10.3390/jcm8010110
|View full text |Cite
|
Sign up to set email alerts
|

MiR-146a-5p Expression in Peripheral CD14+ Monocytes from Patients with Psoriatic Arthritis Induces Osteoclast Activation, Bone Resorption, and Correlates with Clinical Response

Abstract: In psoriatic arthritis (PsA), progressive bone destruction is mediated by monocyte-derived osteoclasts. MicroRNAs (miRNAs) regulate many pathophysiological processes; however, their function in PsA patient monocytes has not been examined. This study aims to address whether specific miRNAs in CD14+ monocytes and monocyte-derived osteoclasts cause active osteoclastogenesis in PsA patients. Candidate miRNAs related to monocyte activation (miR-146a-5p, miR-146b-5p and miR-155-5p) were measured in circulatory CD14+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…However, further experiments are required to elucidate the pathogenic mechanism of action of miR-21-5p in PsA pathogenesis. In support of the observations made in the present study, recent reports demonstrate elevated expression of miR-146a-5p in CD14+ monocytes from patients with PsA compared to both psoriasis patients and HC 35 , and that a single-nucleotide polymorphism in the miR-146a gene was associated with the progression of PsA 36 , an association that appears to be functional in patients with PsA but not RA 37 . Further, in terms of therapeutic response, elevated serum levels of miR-130a-3p in patients with ovarian cancer have been associated with therapeutic resistance to cisplatin 38 , which is consistent with other reports in glioblastoma patients and their response to a temazolamide treatment regimen 6 .…”
Section: Discussionsupporting
confidence: 91%
“…However, further experiments are required to elucidate the pathogenic mechanism of action of miR-21-5p in PsA pathogenesis. In support of the observations made in the present study, recent reports demonstrate elevated expression of miR-146a-5p in CD14+ monocytes from patients with PsA compared to both psoriasis patients and HC 35 , and that a single-nucleotide polymorphism in the miR-146a gene was associated with the progression of PsA 36 , an association that appears to be functional in patients with PsA but not RA 37 . Further, in terms of therapeutic response, elevated serum levels of miR-130a-3p in patients with ovarian cancer have been associated with therapeutic resistance to cisplatin 38 , which is consistent with other reports in glioblastoma patients and their response to a temazolamide treatment regimen 6 .…”
Section: Discussionsupporting
confidence: 91%
“…The current study shows the role of miRNAs in linking transcripts enriched in bone metabolism and immune functions. Many miRNAs are known to regulate bone metabolism, host-microbiome interaction, and inflammatory and immune processes [16,28,29]. MiR-146a affects osteoblast and osteoclast formation in vitro and in vivo miR-146a+/− mice [16,30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we demonstrate that the increased miR-941 expression in CD14+ monocytes from PsA patients enhances osteoclast formation potential and active resorption activity. Our previous study reported that miR-146a-5p expression in CD14+ monocytes of PsA patients correlates with clinical efficacy and inducts osteoclast activation and bone resorption [ 11 ]. In this study, the overall microRNAs were measured using NGS study.…”
Section: Discussionmentioning
confidence: 99%
“…Then, 3 × 10 5 purified human CD14+ monocytes were seeded in 24-well plates containing a-MEM with FBS (10%, v / v ; Invitrogen, Waltham, MA, USA) and M-CSF (20 ng/mL; PeproTech, Rocky Hill, NJ, USA) for three days. RANKL (100 ng/mL; PeproTech, Rocky Hill, NJ, USA) and TNF-α (100 ng/mL; PeproTech, Rocky Hill, NJ, USA) were added to induce osteoclast differentiation [ 11 ]. The osteoclasts were stained with tartrate-resistant acid phosphatase (TRAP) at day 13 using the Acid Phosphate Leukocyte Kit (Sigma, St. Louis, MO, USA) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation